2011
DOI: 10.1016/j.adolescence.2011.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of adolescents’ morality and identity in volunteering. Age and gender differences in a process model

Abstract: The aim of this study was to explain adolescents' volunteering in terms of their morality and identity and to examine the moderation effect of gender and age in this process. Data were collected among 698 Dutch adolescents aged 12 to 20 (M = 15.19; SD = 1.43). Adolescents' moral reasoning was positively associated with understanding moral issues and thinking about public responsibility towards these issues. In turn, moral understanding, along with being personally committed to act upon moral issues, were posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 67 publications
1
28
1
3
Order By: Relevance
“…27,29 However, the findings is not conclusive as there are studies suggest that young females perform better in sense of purpose, which is a component of positive identity. 30 Gender differences was also found in the external asset of support where female participants reporting lower scores on this asset that the male participants, a finding contradictory to the existing literature. Studies have shown that women, in general, report higher levels of perceived support than males.…”
Section: Gender Differences In Internal External and Total Assetscontrasting
confidence: 56%
“…27,29 However, the findings is not conclusive as there are studies suggest that young females perform better in sense of purpose, which is a component of positive identity. 30 Gender differences was also found in the external asset of support where female participants reporting lower scores on this asset that the male participants, a finding contradictory to the existing literature. Studies have shown that women, in general, report higher levels of perceived support than males.…”
Section: Gender Differences In Internal External and Total Assetscontrasting
confidence: 56%
“…Community service, often also referred to as volunteering and service‐learning , can generally be defined as “(often) organized, unpaid activities that are intended to benefit the environment, individuals, groups of people or society” (cf. National Centre for Social Research and the Institute for Volunteering Research, ; van Goethem et al., ). Community service is required for adolescents in some countries (e.g., the Netherlands; Rijksoverheid, ‎) and states (e.g., Maryland; Maryland State Department of Education, n.d.), and is promoted by innumerable national and nongovernmental agencies.…”
Section: How and When Does Community Service Work?mentioning
confidence: 99%
“…To further investigate the correlates of frequent lying, a sample of Study 1 participants was invited to the lab. To assess moral development, a Dutch version of Defining Issues Test (DIT‐2) was used (Rest, Narvaez, Thoma, & Bebeau, ; see van Goethem et al, for the Dutch version). This task is based on presenting subjects with moral dilemmas and asking them to rate and rank different statements as important or unimportant to the decision how to act in such a situation.…”
Section: Studymentioning
confidence: 99%